Circulating folate concentrations and risk of coronary artery disease: a prospective cohort study in Chinese adults and a Mendelian randomization analysis. Issue 3 (11th January 2020) - Long, Pinpin; Liu, Xuezhen; Li, Jun; He, Shiqi; Chen, Huiting; Yuan, Yu; Qiu, Gaokun; Yu, Kuai; Liu, Kang; Jiang, Jing; Yang, Handong; Xu, Chengwei; et al.
ABSTRACT: Background: The association between circulating folate concentrations and risk of coronary artery disease (CAD) has been evaluated in Western populations with inconsistent results; however, the observational and causal associations in Chinese populations with relatively low folate concentrations remain unclear. Objectives: We aimed to examine the association of circulating folate concentrations with incident CAD in Chinese adults, and further evaluated the causal relation using Mendelian randomization (MR) analysis. Methods: We measured baseline serum folate in 1605 incident CAD cases and 1605 age- and sex-matched controls nested within the Dongfeng-Tongji (DFTJ) cohort, which recruited 27, 009 individuals with a mean age of 63.6 y in 2008–2010 and followed up until the end of 2013 (mean: 4.4 y). We quantified the observational association between folate and incident CAD using conditional logistic regression models. A 2-sample MR analysis was performed using summary statistics obtained for genetic variants identified from a genome-wide association study (GWAS) of circulating folate concentrations in participants of European ancestry ( n = 37, 341) and from the CardiogramplusC4D 1000 genomes–based GWAS meta-analysis ( n = 184, 305). We also conducted 1-sample MR among 1545 incident CAD cases and 1444 controls with genotyping data in the DFTJ cohort. Results: In the DFTJ cohort, higher serum folate concentrations were associated with a lower risk of CAD: the OR (95% CI) across sex-specific quartiles of folate (from lowest to highest concentrations) was 1.00 (reference), 0.78 (0.63, 0.97), 0.77 (0.61, 0.97), and 0.75 (0.60, 0.95), respectively ( P -trend = 0.01). In the MR analysis, the OR of CAD per SD increase in genetically predicted serum folate was 1.00 (0.88, 1.14) and 0.88 (0.59, 1.32) for European and Chinese populations, respectively. Conclusions: We found an inverse association between circulating folate concentrations and incident CAD among Chinese populations. However, we confirmed that there was no genetic evidence to support the causal relation in both European and Chinese populations.